2017
DOI: 10.1002/2017wr020458
|View full text |Cite
|
Sign up to set email alerts
|

Managed aquifer recharge through off‐season irrigation in agricultural regions

Abstract: Options for increasing reservoir storage in developed regions are limited and prohibitively expensive. Projected increases in demand call for new long‐term water storage to help sustain agriculture, municipalities, industry, and ecological services. Managed aquifer recharge (MAR) is becoming an integral component of water resources around the world. However, MAR faces challenges, including infrastructure costs, difficulty in enhancing recharge, water quality issues, and lack of available water supplies. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 86 publications
1
77
1
Order By: Relevance
“…Irrespective of the diversion amount for groundwater recharge considered in our simulations, about 34% of the recharged water remained in groundwater storage and about 66% returned to streams as base flow, indicating that Ag‐MAR has the potential to stabilize and locally recover aquifer levels while increasing streamflow during summer low flow periods and the amount of groundwater available for irrigation. Similar groundwater storage gains were found by Niswonger et al () (e.g., 26–29% depending on aquifer hydraulic conductivity) for large‐scale Ag‐MAR simulations in the Carson Valley, NV and Ghasemizade et al () for the eastern San Joaquin Valley, CA. Other large‐scale MAR modeling studies have seen lower gains in groundwater storage (e.g., Ronayne et al, ; Scherberg et al, ); however, most studies observed similar clear benefits of recharge for groundwater‐dependent ecosystems and instream flows.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Irrespective of the diversion amount for groundwater recharge considered in our simulations, about 34% of the recharged water remained in groundwater storage and about 66% returned to streams as base flow, indicating that Ag‐MAR has the potential to stabilize and locally recover aquifer levels while increasing streamflow during summer low flow periods and the amount of groundwater available for irrigation. Similar groundwater storage gains were found by Niswonger et al () (e.g., 26–29% depending on aquifer hydraulic conductivity) for large‐scale Ag‐MAR simulations in the Carson Valley, NV and Ghasemizade et al () for the eastern San Joaquin Valley, CA. Other large‐scale MAR modeling studies have seen lower gains in groundwater storage (e.g., Ronayne et al, ; Scherberg et al, ); however, most studies observed similar clear benefits of recharge for groundwater‐dependent ecosystems and instream flows.…”
Section: Resultssupporting
confidence: 82%
“…Feedback mechanisms between recharge and crop water consumption, crop ET, and water consumption by natural vegetation from elevated soil moisture and groundwater levels could not be estimated in this study because the model does not support simulation of recharge through the root and unsaturated zone. Although such processes are important for enhancing ecosystem services of groundwater‐dependent ecosystems (Bolund & Hunhammar, ; Dillon et al, ; Eamus & Froend, ; Fisher, ), Niswonger et al (), Wu et al (), and Ghasemizade et al () showed that the effect of recharge on crop water consumption and crop ET is modest (e.g., 3–6% increase in crop water consumption over the simulation period; Niswonger et al, ), but the increase in ET by natural vegetation can be significant (e.g., 20–30%; Niswonger et al, ) depending on soil moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…There is interest in expanding use of MAR in CA, both to offset overdraft and to hedge against future decreases in snowpack-water storage and changes in the timing and volume of surface-water availability. Established MAR projects commonly use dedicated infiltration basins located over locally coarse-texture geological deposits to increase recharge, but increasingly, MAR on agricultural fields during nongrowing seasons (Ag-MAR) has been proposed as an alternative to infiltration basins (Dahlke et al 2018;Harter and Dahlke 2014;Niswonger et al 2017). Studies have noted that even during periods of water scarcity, wet-season high-magnitude streamflows (HMF) can often provide ample unmanaged surface water for MAR during nongrowing seasons in CA (Beganskas and Fisher 2017;Kocis and Dahlke 2017) and elsewhere (Chinnasamy et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, these adaptation measures focus on alternative water management strategies to enhance supply and include: reoperating federally managed Truckee River reservoirs to enhance surface water storage under earlier snowmelt regimes [96], constructing a reservoir in the Carson River headwaters to store snowmelt for downstream agricultural irrigation [97], and exploring managed aquifer recharge in the Carson Valley through off-season/winter irrigation in agricultural areas [98].…”
Section: Discussionmentioning
confidence: 99%